2021
DOI: 10.1002/dvdy.329
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and developmental analyses indicate complex functions of calcium‐activated potassium channels in zebrafish embryonic development

Abstract: Background: Calcium-activated potassium channels (KCa) are a specific type of potassium channel activated by intracellular calcium concentration changes. This group of potassium channels plays fundamental roles ranging from regulating neuronal excitability to immune cell activation. Many human diseases such as schizophrenia, hypertension, epilepsy, and cancers have been linked to mutations in this group of potassium channels. Although the KCa channels have been extensively studied electrophysiologically and ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…However, the underlying ion channels and connexins that generate these signals are unknown. Our recent gene expression analysis of calcium-gated potassium channels (KCa) and inwardly rectifying potassium channels (Kir) revealed that many ( kcnn1b , kcnn3 , kcnma1a , kcnma1b , kcnmb2b , kcnmb3 , kcnj4 , kcnj2a , kcnj2b , kcnj11 , kcnj5 , kcnj21 ) have a somite-specific expression at similar developmental stages [ 37 , 38 ]. Their presence in the developing somites may indicate that these channel activities underlie the tissue-level bioelectricity.…”
Section: Discussionmentioning
confidence: 99%
“…However, the underlying ion channels and connexins that generate these signals are unknown. Our recent gene expression analysis of calcium-gated potassium channels (KCa) and inwardly rectifying potassium channels (Kir) revealed that many ( kcnn1b , kcnn3 , kcnma1a , kcnma1b , kcnmb2b , kcnmb3 , kcnj4 , kcnj2a , kcnj2b , kcnj11 , kcnj5 , kcnj21 ) have a somite-specific expression at similar developmental stages [ 37 , 38 ]. Their presence in the developing somites may indicate that these channel activities underlie the tissue-level bioelectricity.…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic and syntenic analyses were performed as we described previously 49,57‐60 . Briefly, multiple protein sequences were aligned using MUSCLE program 61 .…”
Section: Methodsmentioning
confidence: 99%
“…[46][47][48] Thus, the temporal and transient kir genes' expression could be a cellular bioelectric signal for developmental patternings, such as seen in the ectopic somite gene expression of kcnj13 in our long-fin mutant Dhi2059. It is reasonable to speculate that the somite expression of kcnj2a, kcnj11, kcnj5, and other K+ channels (eg, KCa) 49 could be part of a general endogenous fin patterning regulation system for zebrafish fins. In addition, we found multiple genes were expressed in the pectoral fin buds (kcnj2a, kcnj4, kcnj5, kcnj6, and kcnj11), suggesting they might also be involved in fin growth or patterning.…”
Section: Bioelectricity and Developmental Patterningmentioning
confidence: 99%
See 2 more Smart Citations